Post-orogenic sedimentary evolution of the Aquitaine and Bay of Biscay retro-foreland basins (Bartonian to present-day) - (:unkn) unknown (My University, 2019)
Palaeogeographic maps at Africa-scale were drawn with a first attempt of palaeotopographic reconstructions andquantification. This was based on (1) mapping and dating of stepped planation surfaces of pediment/pediplainand etchplain types and (2) the assumption that these stepped planation surfaces result from uplifts combinedwith climatic changes leading to periods of more intense erosion for shaping the pediments/pediplains (see formore arguments Guillocheau et al., 2018, Gondwana Research). Six time intervals were mapped (1) 59-56 Ma(Late Paleocene), (2) 48-41 Ma (Middle Eocene), (3) 34-28 (Early Oligocene), (4) 23-16 Ma (Early Miocene), (5)11-5Ma (Late Miocene) and (6) 5-3 Ma (Early Pliocene). The main outcomes are as follows.(1) Pre-existing relief were created during a major period of uplift during Upper Cretaceous times with remnantsalong the Southern African Plateau (important remnant topography), the future East African and Ethiopian Domesand the Guinean Rise.(2) Paleocene to Late Eocene (66-40Ma) was the time interval during which Africa is (i) near sea level except theremnant relief mentioned before and (ii) intensely weathered.(3) Late Eocene (40 Ma) was a major palaeogeographic reorganization with the initiation of the modern drainages.(4) Oligocene to today (40-0 Ma) was a period of Africa-scale uplifts that reach a paroxysm during uppermostMiocene-lowermost Pliocene times (around 5 Ma).The wavelength of the topographies created since 40 Ma are higher than 1000 km and sometimes longer (e.g.all North Africa). This means that their causes of uplift can only be related to mantle dynamics. Nevertheless,denudation data (e.g. thermochronology) shows that most of the denudation was located along the “coastal” plainsof Africa or on the rift flanks (with the noticeable exception of the Congo catchment).These observations suggest that the South African superplume had a significant role in the growth of thesetopographies since 40 Ma, with a propa
Keywords: African Research